2017
DOI: 10.1002/aur.1877
|View full text |Cite
|
Sign up to set email alerts
|

Everyday executive function predicts adaptive and internalizing behavior among children with and without autism spectrum disorder

Abstract: We examined whether parents' ratings of their children's flexibility and ability to monitor their behavior predicted adaptive skills (e.g., ability to complete day-to-day personal tasks, communicate, and socialize) and symptoms of anxiety and depression among children with and without autism spectrum disorder. For both groups, children's abilities to manage and monitor their behavior were strongly related to adaptive skills. Children's flexibility and ability to inhibit inappropriate behavior and control their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
47
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 60 publications
10
47
1
2
Order By: Relevance
“…Nevertheless, our results seem to be consistent with previously reported findings that metacognitive abilities (which include working memory along other EF skills) predicted conceptual skills 36,37,39,40 , and other studies that found inhibition 41 and flexibility 42 to be significantly correlated with conceptual skills. Interestingly, all studies that found metacognitive abilities as better predictors of conceptual skills used caregiver (mostly parents) reports of everyday executive functions 36,37,39,40 , while the studies that highlighted the importance other core EF: inhibition 41 and flexibility 42 , used tests that measured EF directly in the participant. Based on this, we hypothesised that working memory would play a more significant role in the execution of activities related to conceptual skills at home, a more predictable setting where the need to learn and perform new skills occurs less frequently than in a school setting.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, our results seem to be consistent with previously reported findings that metacognitive abilities (which include working memory along other EF skills) predicted conceptual skills 36,37,39,40 , and other studies that found inhibition 41 and flexibility 42 to be significantly correlated with conceptual skills. Interestingly, all studies that found metacognitive abilities as better predictors of conceptual skills used caregiver (mostly parents) reports of everyday executive functions 36,37,39,40 , while the studies that highlighted the importance other core EF: inhibition 41 and flexibility 42 , used tests that measured EF directly in the participant. Based on this, we hypothesised that working memory would play a more significant role in the execution of activities related to conceptual skills at home, a more predictable setting where the need to learn and perform new skills occurs less frequently than in a school setting.…”
Section: Discussionsupporting
confidence: 93%
“…The present study also found that prior estimates of everyday EF were predictive of key outcomes in ASD: emotional (i.e., anxiety/depression symptoms), behavioral (i.e., aggressive/oppositional behavior) and overall social functioning, consistent with the recent study by Gardiner and Iarocci (2018) of youth with ASD at a single time point. Specifically, behavioral regulation (i.e., BRIEF BRI) difficulties at baseline predicted internalizing symptoms (anxiety and depression) 2 years later in children with ASD.…”
Section: Discussionsupporting
confidence: 90%
“…The EF challenges that children with ASD face may not be observable in highly structured laboratory settings [Kenworthy, Yerys, Anthony, & Wallace, 2008] but are frequently identified by parents [Gardiner & Iarocci, 2018]. This research examined caregiver reports of everyday EF using the Behavior Rating Inventory of Executive Functioning, Version 2 [BRIEF‐2; Gioia, Isquith, Guy, & Kenworthy, 2015].…”
Section: Introductionmentioning
confidence: 99%